IMPLEMENTASI VISI COSMOTHEANDRIC RAIMON PANIKKAR DALAM PENDIDIKAN ISLAM - Natsir, Ahmad (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2023)
This article aims to discuss Raimon Panikkar’s religious theory, which he calls the Cosmotheandric Vision. This theory is the result of Panikkar’s experience of navigating religious life. Then this theory is implemented in learning management in the classroom. Therefore, Islamic education has always been directed at the transmission of rigid dogmas, which have resulted a generation that is less tolerant of differences. Meanwhile, at the same time, the seeking for a moderate learning model is still under debate and long discussion. This article answers at least two basic questions. First, how to explain the theory of Cosmotheandric Vision. This Cosmotheandric Vision emphasizes differences as part of the difference in the universe. Although the universe has different parts, all of them lead to one vision, complementing the others to get in harmony with direction of universe. Second, how to implement the theory of Cosmotheandric Vision in Islamic education. Islamic education has basically introduced the closing concept with the sentence “wallahu a’lam”. This sentence is in line with Raimon Panikkar’s cosmos view, which explains that the logos will never be able to achieve God’s truth (theos). The word “wallahu a’lam” has to be implemented in more depth regarding of truth the difference that the owner of truth is only One, Allah, while what educators teach is just a “belief” wich is far from the word “faith”.